Astrovirus VA1 in patients with acute gastroenteritis. Issue 2 (17th January 2021) - Lanave, Gianvito; Loconsole, Daniela; Centrone, Francesca; Catella, Cristiana; Capozza, Paolo; Diakoudi, Georgia; Parisi, Antonio; Suffredini, Elisabetta; Buonavoglia, Alessio; Camero, Michele; Chironna, Maria; Martella, Vito
Abstract: Human astroviruses (AstVs) are usually associated with acute gastroenteritis. In recent years, atypical animal‐like AstVs have been identified, but their pathogenic role in humans has not been determined. Starting from 2010, there has been a growing evidence that AstVs may also be associated with encephalitis in human and animal hosts. Some human atypical AstV strains (VA1, MLB1/MLB2) display neurotropic potential, as they have been repeatedly identified in patients with AstV‐related encephalitis, chiefly in immunosuppressed individuals. In this study, a VA1‐like AstV was identified from a single stool sample from an outbreak of foodborne acute gastroenteritis occurred in Italy in 2018. On genome sequencing, the virus was related to the VA1‐like strain UK1 (99.3% at the nucleotide level). Similar viruses were also found to circulate in paediatric patients hospitalized with AGE in the same time span, 2018, but at low prevalence (0.75%, 3/401). Gathering epidemiological data on atypical AstVs will be useful to assess the risks posed by atypical AstV infections, chiefly in medically fragile patients.